Analysis of Beef Halal Critical Points with Halal Logistics Approach and Risk Management - Nabila Noor Qisthani; Syarif Hidayatuloh; Yulinda Uswatun Kasanah (Jurnal Ilmiah Teknik Industri, 2023)
The increase in the number of certified halal products shows the Indonesian people's increasing level of awareness of the halalness of a product. In addition, people are also increasingly curious about all the activities involved along the supply chain to ensure whether the products they buy are genuinely halal. One of the consumer products that need to be traced to the halal supply chain is beef products because there is a risk of contamination throughout the supply chain from raw materials, production processes, distribution, storage and handling. Calculation of risk in this study will use the House of Risk (HOR) method. This research focuses on the process of inbound and outbound logistics and the beef slaughtering process at the Purwokerto Slaughterhouse. The results of this study obtained 26 risk events and 28 risk agents. Based on risk mapping using phase 1 and Pareto HOR diagrams, 11 risks are prioritized based on the highest ARP values, namely A15, A25, A19, A7, A5, A28, A6, A2, A16, A17, and A21. Moreover, it made 14 recommendations for mitigation actions that the company can apply to control these risks.